Numerical design and optoelectronic simulation of a germanium-on-silicon PIN photodetector for high-speed optical communication systems - Ashenafi Abera Gebre; Kedir Botamo Adem (FoundAE, 2026)
Background: The rising demand for fast optical communication systems in the telecommunications industry, data centers, aerospace, and defense applications has made it imperative to design photodetectors with high responsivity, minimum dark current, and broad bandwidth. Germanium on Silicon (Ge-on-Si) PIN photodetectors are potential contenders in this regard due to their high optical absorption capability at the telecommunication wavelengths as well as CMOS silicon photonics compatibility. Optimizing their optoelectronic performance is an important issue, however. Aims: In this research, we intend to numerically design, optimize, and evaluate a Ge-on-Si PIN photodetector via a coupled optoelectronic simulation technique for high optical absorption, high responsivity, low dark current, and high speed operation in advanced optical communication systems. Method: The designed photodetector was modeled and simulated by using Lumerical FDTD Solutions and Lumerical DEVICE software. A combined simulation method of optical-electrical was utilized to simulate optical field distribution, optical absorption, carrier generation, photocurrent, dark current, and 3dB-bandwidth of the device. Structural parameters were carefully optimized to enhance the performance of the device for telecommunication operation. Result: The optimized Ge-on-Si PIN photodetector resulted in the optical absorption of about 92% at 1550 nm wavelength, peak responsivity of 0.84 A/W, and the minimum value of the dark current was 0.9 μA at reverse bias voltage V. The calculated 3-dB bandwidth was 45 GHz. The increase in dark current with temperature due to the generation of carriers from thermal energy was also observed through simulations. Conclusion: The designed Ge-on-Si PIN detector offers a well-balanced structure, providing excellent responsivity, low dark current, and large bandwidth, which makes it a very promising device for silicon photonics and high-speed optical communication in the future. Besides, there is a great possibility to apply this detector for defense and aerospace applications such as optical communication for military and satellites and other systems requiring high-performance optical connections.